2019
DOI: 10.1016/j.eurpsy.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of brain activity with transcranial direct current stimulation: Targeting regions implicated in impaired illness awareness in schizophrenia

Abstract: Background: Impaired illness awareness or insight into illness (IIA) is a common feature of schizophrenia that contributes to medication nonadherence and poor clinical outcomes. Neuroimaging studies suggest IIA may arise from interhemispheric imbalance in frontoparietal regions, particularly in the posterior parietal area (PPA) and the dorsolateral prefrontal cortex (dlPFC). In this pilot study, we examined the effects of transcranial direct current stimulation (tDCS) on brain regions implicated in IIA. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 56 publications
(78 reference statements)
0
20
0
Order By: Relevance
“…We selected six RCTs [ 39 , 40 , 41 , 42 , 43 , 44 ], three open-label studies [ 45 , 46 , 47 ], one case series [ 48 ] and four case reports [ 49 , 50 , 51 , 52 ]. The studies came from five independent research groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We selected six RCTs [ 39 , 40 , 41 , 42 , 43 , 44 ], three open-label studies [ 45 , 46 , 47 ], one case series [ 48 ] and four case reports [ 49 , 50 , 51 , 52 ]. The studies came from five independent research groups.…”
Section: Resultsmentioning
confidence: 99%
“…In total, the included studies recruited 226 patients, with mean age ranging from 24 to 46.4 and a sex-ratio of 1.073 (117 males and 109 females). Almost all the patients were right-handed: Nine studies included exclusively right-handed patients [ 40 , 41 , 43 , 44 , 45 , 48 , 50 , 51 , 52 ]; two studies reported to have included mixed samples with non-right-handed patients [ 39 , 47 ]; three studies did not provide information regarding handedness; and Kim et al (2019) reported a mean score of 77.6 ± 16.2 at the Edinburgh Handedness Inventory [ 53 ]. Most of the patients included were on antipsychotic medication but two case-reports included drug-free patients [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations